2020
DOI: 10.3390/ijms21041470
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization with Insect Cecropin A (1–8) Improve the Stability and Selectivity of Naturally Occurring Peptides

Abstract: Antimicrobial peptides (AMPs) offer great hope and a promising opportunity to overcome the rapid development of drug-resistant pathogenic microbes. However, AMPs often lack the stability required for a successful systemic drug. Hybridizing different AMPs is a simple and effective strategy to obtain novel peptides. N-terminal fragment of cecropin A (CA (1-8)) is often used to hybridize with other AMPs to reduce cytotoxicity. However, hybridizing with CA (1-8) in improving the stability of AMPs is not clear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
0
12
0
6
Order By: Relevance
“…In addition, the α-helical hybrid peptide CA-FO (charge of +13), which comprised cecropin A (charge of +5) (CA (1–8)) and the most potent region of fowlicidin-2 (charge of +9)(FO (1–15)), exhibited the greatest antibacterial activity against both Gram-positive and Gram-negative bacteria. Furthermore, CA-FO can also damage the membrane integrity and increase membrane permeability [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the α-helical hybrid peptide CA-FO (charge of +13), which comprised cecropin A (charge of +5) (CA (1–8)) and the most potent region of fowlicidin-2 (charge of +9)(FO (1–15)), exhibited the greatest antibacterial activity against both Gram-positive and Gram-negative bacteria. Furthermore, CA-FO can also damage the membrane integrity and increase membrane permeability [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, significant loss of activity was not seen until 4 h of pre-incubation. In contrast, SynPG-1 was found to retain its activity after pre-incubation in porcine serum for at least 24 h. Recently, Yang et al ran a similar experiment for their design of hybridized insect cecropin A and Fowlicidin-2, which retained high antimicrobial activity after 2 h of pre-incubation in 12.5%, 25%, and 50% human serum [63]. Similarly, a truncated analogue of the snake venom cathelicidin-like peptide crotalicidin has been reported as having exceptionally high stability of human serum for up to 12 h of incubation [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have shown that it's essential for AMPs to ploy biological activities and primary mechanism of action that the positive charges and hydrophobic properties (Figure 1A). The electrostatic interaction, that between AMPs and the negatively charged bacterial membrane, can be promoted by the positive charges; while the bilayer of the bacterial membrane can be inserted by AMPs though hydrophobicity, which leads to the cell membrane be disrupted and permeabilitied, and the bacterial contents be leakaged and death, eventually (20)(21)(22). On the other hand, some AMPs, which can make membrane transporters blocked and cell division inhibited and can interact with nucleic acids and/or with the protein biosynthesis process, function differently and act in a non-lytic manner, preferring intracellular targets (23)(24)(25).…”
Section: Biological Function and Active Mechanism Of Amps Antibacterial Function And Active Mechanism Of Ampsmentioning
confidence: 99%